2010
DOI: 10.1213/ane.0b013e3181d3e80b
|View full text |Cite
|
Sign up to set email alerts
|

Levobupivacaine 0.5% Provides Longer Analgesia After Sciatic Nerve Block Using the Labat Approach Than the Same Dose of Ropivacaine in Foot and Ankle Surgery

Abstract: Twenty milliliters levobupivacaine 0.5% in posterior gluteal (Labat) sciatic nerve block provided longer-lasting analgesia after foot and ankle surgery compared with the same dose of ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 8 publications
1
28
0
3
Order By: Relevance
“…Cline et al and Fournier et al had made similar observations. 14,15 In the present study, intra operative and postoperative haemodynamic parameters were also studied. The pulse rate, systolic blood pressure, diastolic blood pressure and oxygen saturation were comparable in both the groups' intra operatively and post operatively.…”
mentioning
confidence: 99%
“…Cline et al and Fournier et al had made similar observations. 14,15 In the present study, intra operative and postoperative haemodynamic parameters were also studied. The pulse rate, systolic blood pressure, diastolic blood pressure and oxygen saturation were comparable in both the groups' intra operatively and post operatively.…”
mentioning
confidence: 99%
“…Levobupivacaine administered via a peripheral nerve block continuous catheter provides excellent post-operative analgesia and decreases the post-operative systemic opioids requirements . (13,14,15,16) It has been postulated that presynaptic activation of alpha-2A adrenoceptor in the locus ceruleus inhibits the release of nor-epinephrine and results in the sedative and hypnotic effects and terminates the propagation of pain signals leading to analgesia. High selectivity for alpha 2A receptors mediates analgesia, sedation and anxiolysis.…”
Section: Figurementioning
confidence: 99%
“…1 A recent clinical trial comparing levobupivacaine 0.5% with ropivacaine 0.5% for the management of postoperative ankle surgery pain found that levobupivacaine provide more long lasting postoperative analgesia compared with the same dose of ropivacaine, in contrast McNamee et al reported that intrathecal administration of 17.5 mg plain ropivacaine 0.5% or plain bupivacaine 0.5% resulted in similarly effective anesthesia for total hip arthroplasty. 2,3 We have planned the study to evaluate effect of plain ropivacaine 0.5% versus plain levobupivacaine 0.5% in gynecological surgeries.…”
Section: Introductionmentioning
confidence: 99%